Plasma volume is associated with micronutrient mass but not concentration in healthy US women of reproductive age - Sixtus Aguree; Leigh A. Martin; Alison D. Gernand (Journal of Trace Elements and Minerals)
Background: Plasma transports nutrients and composes more than half of the volume of blood. A few prior studies suggest that plasma volume fluctuations may impact certain micronutrient concentrations. We hypothesized a slight negative correlation between plasma volume and micronutrient biomarkers throughout the menstrual cycle in healthy women of reproductive age (n = 45). Methods: The study involved three visits during one menstrual cycle where fasting blood samples were taken to measure biomarker concentrations for zinc, copper, magnesium, manganese, iron, ferritin, retinol, and hemoglobin. A bolus dose of indocyanine green (ICG; equivalent to 0.25 mg.kg-1 of body weight) was injected to measure plasma volume. The total circulating micronutrient biomarker mass was calculated using the plasma volume and biomarker concentration. We used Spearman's correlation and fractional polynomial regression techniques to assess the relationship between plasma volume and biomarker concentration and mass. Results: Plasma volume ranged from 1210 to 3520 mL. During all three visits, the correlation between micronutrient biomarker concentrations and plasma volume ranged from -0.05 to 0.10 (all P > 0.05); However, there was a strong positive correlation between biomarker mass and plasma volume, ranging from 0.26 to 0.95 (all P < 0.05). Five of the eight biomarkers examined (zinc, copper, magnesium, retinol, and hemoglobin) showed a correlation coefficient > 0.70 (P < 0.001) between mass and plasma volume. Conclusion: Our findings indicate that biomarker concentrations are maintained across a range of plasma volume, suggesting that plasma volume may not be necessary to interpret micronutrient status in healthy non-pregnant women of reproductive age.